IDDF2020-ABS-0162 Trends in hospitalised drug-induced liver injury from 2009 to 2019 – the rise of non-prescription medications. (18th November 2020) - Nash, Emily; Majumdar, Avik; McCaughan, Geoffrey; Strasser, Simone; Liu, Ken
Abstract : Background: Drug-induced liver injury (DILI) is the most common cause of acute liver failure (ALF) in Western countries. We studied the characteristics and outcomes of non-paracetamol DILI. Methods: We retrospectively studied patients admitted to a state-wide quaternary-referral liver transplant (LT) centre for DILI between 2009–2019. Cases were identified by ICD-10 diagnosis code K71. Primary outcome was LT-free survival at 90 days. Results: During the study period, 65 cases of DILI due to non-paracetamol drugs were admitted (57% female, median age 53). A minority had chronic liver disease (20%) or psychiatric disease (26%). The most common implicated drugs are shown in figure 1 . Implicated drugs for hospitalised non-paracetamol DILI patients. While overall number of admissions remained stable over time, the proportion due to non-prescription drugs significantly increased (0% 2009–10, 24% 2011–13, 18% 2014–16, 53% 2017–19, P=0.009). The majority of patients were symptomatic (92%): jaundice (68%), abdominal pain (35%), fever (17%) and rash (15%). Hepatic encephalopathy was present in 32%. Laboratory patterns of DILI were: hepatocellular (R value>5) 54%, cholestatic (R<2) 28% and mixed (R=2–5) 19%. Hy's law was met in 48% while 26% had ALF (encephalopathy + INR > 1.5). The median admission MELD score was 21. 35% of patients received corticosteroids, and 15% received ursodeoxycholic acid. ICU admission and haemodialysis occurred in 35% and 11%, respectively. During the study period, there were 12 deaths and 12 LT. The 90-day LT-free survival was 71%. Univariate predictors for LT or mortality at 90 days were: jaundice (HR 9.77, P=0.027), encephalopathy (HR 2.70, P=0.036), hepatocellular pattern (HR 2.85, P=0.047), fulfilling Hy's Law (HR 2.71, P=0.046) and MELD (HR 1.14, P<0.001). On multivariable analysis, only MELD remained predictive of worse 90-day LT-free survival (HR 1.14 per point increase, P<0.001). Conclusions: At this LT centre, 30% of patients hospitalised for non-paracetamol DILI experienced death or LT at 90 days. The proportion of cases due to non-prescription drugs increased over time. MELD score predicted for adverse outcomes.